Effect of docosahexaenoic acid‐enriched fish oil supplementation in pregnant women with Type 2 diabetes on membrane fatty acids and fetal body composition—double‐blinded randomized placebo‐controlled trial. Issue 11 (28th June 2014) - Min, Y.; Djahanbakhch, O.; Hutchinson, J.; Bhullar, A. S.; Raveendran, M.; Hallot, A.; Eram, S.; Namugere, I.; Nateghian, S.; Ghebremeskel, K.
Abstract Aims To test if docosahexaenoic acid‐enriched fish oil supplementation rectifies red cell membrane lipid anomaly in pregnant women with Type 2 diabetes and their neonates, and alters fetal body composition. Methods Women with Type 2 diabetes (n = 88; 41 fish oil, 47 placebo) and healthy women (n = 85; 45 fish oil, 40 placebo) were supplemented from the first trimester until delivery. Blood fatty acid composition, fetal biometric and neonatal anthropometric measurements were assessed. Results A total of 117 women completed the trial. The women with Type 2 diabetes who took fish oil compared with those who received placebo had higher percentage of docosahexaenoic acid in red cell phosphatidylethanolamine in the third trimester (12.0% vs. 8.9%, P = 0.000) and at delivery (10.7% vs. 7.4%, P = 0.001). Similarly, the neonates of the women with Type 2 diabetes supplemented with the fish oil had increased docosahexaenoic acid in the red cell phosphatidylethanolamine (9.2% vs. 7.7%, P = 0.027) and plasma phosphatidylcholine (6.1% vs. 4.7%, P = 0.020). Docosahexaenoic acid‐rich fish oil had no effect on the body composition of the fetus and neonates of the women with Type 2 diabetes. Conclusions A daily dose of 600 mg of docosahexaenoic acid was effective in ameliorating red cell membrane docosahexaenoic acid anomaly in pregnant women with Type 2 diabetes and neonates, and in preventing the decline of maternal docosahexaenoic acid during pregnancy. We suggest that the provision of docosahexaenoic acid supplement should be integrated in the antenatal care of pregnant women with Type 2 diabetes.